Analysis of the Relationship Between Entrepreneurship and Trade Openness within the Framework of Quantile Panel Approach: The Case of OECD Countries - Safiullah Salangi; Sezer Kahyaoglu (İzmir İktisat Dergisi)
This study aims to examine the impact of the trade openness of selected OECD countries on entrepreneurship. There is a general acceptance that the impact of the trade openness of economies on entrepreneurship is positive. In the analysis process, econometric modeling studies were carried out based on the data of the selected OECD countries for the 2006-2020 period. The quantile panel regression technique was used to test the impact of trade openness on entrepreneurship. The quantile panel regression analyses have been carried out with an approach that considers the asymmetric situation between the selected OECD countries. Hence, this approach has been a contribution to the literature. Policy recommendations are presented within the framework of empirical findings. According to the empirical findings, entrepreneurship activities are important in terms of increasing economic performance in the selected OECD countries and show that policies should be implemented in support of entrepreneurship activities. The necessity of considering the impact of the trade openness level on entrepreneurship in determining policies has been revealed. In particular, the fact that the economies assess this issue in the policy development process can be considered a strategic instrument.